2014
DOI: 10.1038/mtm.2013.9
|View full text |Cite
|
Sign up to set email alerts
|

Empty virions in AAV8 vector preparations reduce transduction efficiency and may cause total viral particle dose-limiting side effects

Abstract: Empty virions are inadvertent by-products of recombinant adeno-associated virus (rAAV) packaging process, resulting in vector lots with mixtures of full and empty virions at variable ratios. Impact of empty virions on the efficiency and side-effects of rAAV transduction has not been well characterized. Here, we generated partially and completely empty AAV8 virions, fully packaged rAAV8 lots as well as mixtures of empty and fully packaged virions with variable ratios of empty virions (REVs). The aforementioned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
96
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(99 citation statements)
references
References 30 publications
2
96
1
Order By: Relevance
“…These data tabulated in (Table 1) suggest that total capsid (cp) doses of at least 1 × 10 12 cp/kg may be necessary to surmount even low level of preexisting NAbs. Indeed, Mingozzi et al showed in a mouse model of anti-AAV NAbs that empty capsids can enhance FIX transgene expression in a dose-dependent manner that is also a function of NAb titer; however, excessive empty capsids also lead to decreased transgene expression, likely due to competition with vector at cellular binding sites [24] since the addition of empty capsids significantly decreases transduction in mice without NAbs [25]. Together, the human and mouse data suggest that reintroduction of empty viral capsids is a promising strategy for avoiding NAbs, especially at low titer levels.…”
Section: Overcoming Immune Responses To Aavmentioning
confidence: 99%
“…These data tabulated in (Table 1) suggest that total capsid (cp) doses of at least 1 × 10 12 cp/kg may be necessary to surmount even low level of preexisting NAbs. Indeed, Mingozzi et al showed in a mouse model of anti-AAV NAbs that empty capsids can enhance FIX transgene expression in a dose-dependent manner that is also a function of NAb titer; however, excessive empty capsids also lead to decreased transgene expression, likely due to competition with vector at cellular binding sites [24] since the addition of empty capsids significantly decreases transduction in mice without NAbs [25]. Together, the human and mouse data suggest that reintroduction of empty viral capsids is a promising strategy for avoiding NAbs, especially at low titer levels.…”
Section: Overcoming Immune Responses To Aavmentioning
confidence: 99%
“…Most of the negatively stained pseudo-vectors appeared to be empty because they displayed donut-like shapes of virions, and no significant difference was found among the three types of pseudo-vectors (Figure 3A) 15 . We also did not observe self-assembly intermediates, which should be smaller than the regular particles 20 .…”
Section: Resultsmentioning
confidence: 73%
“…Recently, Gao et al. demonstrated that pseudo-vectors suppressed transgene expression and contributed to hepatic transaminase elevation in mice 15 . Moreover, the pseudo-vectors cogenerated and separated from the bona fide AAV8 vectors, resulting in higher elevations of liver enzyme than the vector alone or mixed with a completely empty vector.…”
Section: Introductionmentioning
confidence: 99%
“…Immunogenicity of AAVs may be exacerbated by empty capsid contamination in viral preparations 35,36 . The viral purification protocol (Steps 15-31) provided here reduces, but does not eliminate, empty capsids (Fig.…”
Section: Limitations Of the Methodsmentioning
confidence: 99%